Comparação entre ticagrelor e prasugrel na inibição do receptor P2Y12 em pacientes submetidos a terapia fármaco-invasiva: estudo randomizado sampa - Guimaraes, Leonardo de Freitas Campos [UNIFESP] (2018)
Background: A pharmacodynamic comparison between ticagrelor and prasugrel after fibrinolytic therapy has not yet been performed. Methods: In the singlecenter, 50 consecutive STelevation myocardial infarction (STEMI) patients previously treated with clopidogrel and undergoing a pharmacoinvasive strategy were randomized to either a ticagrelor (n = 25) 180 mg loading dose followed by 90 mg bid, or a prasugrel (n = 25) 60 mg loading dose followed by 10 mg/day, initiated after fibrinolytic therapy but before angiography. Platelet reactivity was assessed with the VerifyNow P2Y12 assay at 0, 2, 6, and 24 h after randomization. Results: Mean times from fibrinolysis to prasugrel or ticagrelor administration were 11.1 ± 6.9 and 13.3 ± 6.3 h, respectively (p = 0.24). The values of PRU decreased significantly from baseline to 2 h (p < 0.001) and from 2 h to 6 h (p < 0.001) in both groups. There was no difference in PRU values between 6 h and 24 h. The mean PRU values at 0, 2, 6, and 24 h were 234.9, 127.8, 45.4, and 48.0 in the prasugrel group and 233.1, 135.1, 67.7, and 56.9 in the ticagrelor group, respectively. PRU values did not significantly differ between groups at any time period of the study. Conclusions: In patients with STEMI treated with fibrinolytic therapy, platelet inhibition after clopidogrel is suboptimal and can be further increased with more potent agents. Ticagrelor and prasugrel demonstrated a similar extent of P2Y12 receptor inhibition within 24 h, although maximal platelet inhibition after these potent agents was not achieved for 6 h.